Gaps between Alarm Capabilities and Decision-making Needs: An Observational Study of Detecting Patient Decompensation. Issue 1 (June 2018) - Horwood, Chelsea R.; Rayo, Michael F.; Fitzgerald, Morgan; Balkin, E. Asher; Moffatt-Bruce, Susan D.
Decompensation is a change in the overall ability to maintain physiological function in the presence of a stressor or disease. In the medical setting, clinicians utilize a wide range of technological tools to aid in their clinical decision making and to identify early warning signals for decompensation. However, many of these technologies have underperformed and are not aligned with the actual role of practitioners, resulting in unintended consequences and adverse events. The primary aim of this study is to explore how different nurses interpret early warning signs in order to anticipate decompensation. The secondary aim is to assess which technologies nurses rely on when anticipating decompensation, and if those technologies are adequately aiding them in their clinical decision making. Two researchers performed semi-structured ethnographic interviews that were recorded and transcribed during the summer of 2017. In total, 43 nurses were interviewed from different medical and surgical floors within the same hospital. Participants were asked questions focused on how they use and respond to alarms and how they anticipate patient decompensation. Constant Comparative Analysis was used to reveal patterns of responses between participants. Based on the qualitative analysis 6 major themes emerged: 1. Anticipating patient decompensation requires creating a complete mental "picture of the patient" by the nurses 2. Nurse-to-nurse communication and expertise is essential to understanding the patient's history 3. Warning signs for decompensation were largely determined by a patient's baseline 4. Change over time, or trends, is informative for anticipating decompensation. Numbers (regarding vital signs and labs) alone are not 5. Consistent care of patients improved nurse's confidence in decision making 6. Anticipating decompensation requires "staying ahead of the machines Our research suggests that there is a gap between the information practitioners need to accurately anticipate patient decompensation, and the information current alarm technologies provide. Alarms are the primary tool provided to nurses to aid them in detecting hazardous events, however, current alarms are not well-suited in supporting signals that anticipate patient decompensation before it happens.